Pelatihan Peningkatan Minat Berwirausaha dan Pemanfaatan Media Sosial untuk Mewujudkan Ekonomi Mandiri Bagi Para Ibu Rumah Tangga di Desa Jero Gunung Kecamatan Sakra Barat - Hartiani Hartiani; Intan Mawaddah; Siti Sofa Marwati; Zainurrofik Zainurrofik; M. Hazril Wahyudi; Sahinun Sahinun; Diar Miswatul Azizah; Mizan Hadi; Irwan Rosyadi; Siska Endah Wahyu Anggraeni; Yuli Eli Ana; Syahruddin Syahruddin (Jurnal Pelayanan Masyarakat, 2024)
This training aims to increase entrepreneurial interest and ability to utilize social media among housewives in Jero Gunung Village, West Sakra District, East Lombok. In today's digital era, social media has become an effective tool for promoting products and services, as well as expanding market reach. However, many housewives still lack understanding on how to utilize it optimally. This training activity consisted of educational sessions on the basics of entrepreneurship, marketing strategies, and the use of social media as a business platform. In addition, this training also provides assistance in planning and managing small businesses that have the potential to increase family income and realize an independent economy. The results of the training showed an increase in participants' knowledge and skills in entrepreneurship, as well as their increased confidence to start a new business or develop an existing one. Thus, this training is expected to have a positive impact on the family economy and community welfare in Jero Gunung Village.